PENERAPAN STRATEGI THINK TALK WRITE DALAM MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X.4 SMA NEGERI 7 PEKANBARU - Lestari, Tatik (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to improve mathematics achievement by applying think talk write strategy in the cooperative learning. The research is classroom action research. The subject of this research is students of class X.4 SMAN 7 Pekanbaru in the second semester academic years 2014/2015, there are 32 students in the class, consist of 12 boys and 20 girls. This research is exercised in two cycles, and at the end of every cycle carried out mathematics achievement test. Data collecting through observation and written test. The observation was doing for the observation of learning activity of teacher and student. Base on the resultof analysis, the amount of students that reaching KKM interest improves from 40,6% at early score and become 50,0% at the first cycle and become 65,6% at the second cycle. The result of research conclude that applying think talk write strategy in the cooperative learning can improves mathematics achievement X.4 SMAN 7 Pekanbaru in the second semester academic years 2014/2015.Key Word : Mathematics learning outcome, Think talk write strategy in the cooperative learning, Classroom Action Research.